From stress to growth : strengthening Asia's financial systems in a post-crisis world - Noland, Marcus, 1959-; Park, Donghyun (Washington, DC : Asian Development Bank : Peterson Institute for International Economics, 2015)
"Asian financial systems, which serve the most economically dynamic region of the world, survived the global economic crisis of the last several years. In this book scholars argue in separate essays that Asian systems must strengthen their quality, diversity, and resilience to future shocks in order to deliver growth in coming years. The book examines such phenomena as the dominance of state-owned banks, the growth of nonbank lending (the so-called shadow banks), and the need to develop local bond markets, new financial centers, and stronger supervisory tools to prevent dangerous real estate asset bubbles. China's large financial system is discussed at length, with emphasis on concerns that China's system has grown too fast, that it is overly tilted toward corporate borrowing, and that state domination has led to overly easy credit to state-owned actors. Asia needs investment to improve its infrastructure and carry out technological innovation, but the book argues that the region's financial systems face challenges in meeting that need"--
Financing productivity- and innovation-led growth in developing Asia : international lessons and policy issues -- China : maintaining financial stability amidst financial liberalization -- Bank stress tests and financial stability : lessons from the 2009-14 U.S. and EU-wide tests for Asian emerging economies -- The financial sector and growth in emerging Asian economies -- Financial development and output growth in developing Asia and Latin America : a comparative sectoral analysis.
"June 2015."
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Finance -- Asia; Financial crises -- Asia; Asia -- Economic conditions -- 21st century; Electronic books